Dynamics of language grounding: on the time course, durability, adaptability, and vulnerability of embodied effects - Kogan, Boris; Birba, Agustina; Díaz Rivera, Mariano; González Santibáñez, Catalina; García, Adolfo M. (Frontiers in Psychology, 2025)
From an embodiment stance, semantic processes reactivate specialized brain networks supporting daily experiences. While this general claim has been amply supported, key questions remain unanswered regarding the time course, durability, adaptability, and vulnerability of the underlying mechanisms. This work reviews the main findings on these topics, based on behavioral, neuropsychological, neuroanatomical, hemodynamic, magnetoencephalographic, electroencephalographic, and intracranial methods. The evidence suggests that language-induced sensorimotor reactivations are (a) primary and extended during the temporal flow of meaning, (b) enduring as an anchor for verbal learning throughout life, (c) responsive to individual experiences, and (d) selectively vulnerable to diverse brain alterations. Such conclusions have theoretical, educational, and clinical implications, affording constraints for neurolinguistic models, innovations in language teaching, and early markers of brain disorders. These insights deepen our understanding of the neurocognitive phenomena shaping daily language use.